A Case Analysis On Sony Electronics Corporations - Akyaa Ahwoi, Nana Adwoa (2004)
This case study is divided into two sections: Case Writing and Case analysis. Case Writing provides the general information on SONY, its organizational structure, achievements, products and financial information.This section also gives an insight into SONY's core business unit, which is the electronics segement.The case analysis section highlights environmental analysis, SWOT analysis, financial analysis, competitive analysis and diagnosis of SONY.